Health care providers, institutions, and patients : changing patterns of care provision and care delivery - Kronenfeld, Jennie J. (Research in the sociology of health care ;, 2000)
This volume explores issues connected with health care providers, institutions, and patients. The focus of many of the articles is on changing patterns of care delivery and provision of care, as it affects these important groups of actors within the health care system. The articles range from those that focus on more specialized groups of patients, such as the elderly, to those that focus on people who deliver health care services to those that deal with more general issues of the restructuring of the US health care system.